2016
DOI: 10.1634/theoncologist.2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Referral Criteria for Outpatient Palliative Cancer Care: A Systematic Review

Abstract: Outpatient clinics are increasingly being recognized for their critical role in facilitating early palliative care access. This systematic review highlighted the lack of consensus in the literature on which patients should be referred in the ambulatory setting. Cancer diagnosis, prognosis, physical symptoms, performance status, psychosocial distress, and end-of-life care planning needs may be taken into consideration when appropriate candidates are being identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 44 publications
3
99
0
8
Order By: Relevance
“…14e17 More research is needed to understand the barriers to earlier referral to palliative care for such patients. 18,19 The data also suggest that patients with low or no insurance had a higher number of palliative care visits, which is consistent with the findings of higher physical and psychosocial distress and higher risk of aberrant opioid use. At the same time, it is reassuring to find that insurance status was not a barrier to continued provision of palliative care services once access was established.…”
Section: Discussionsupporting
confidence: 82%
“…14e17 More research is needed to understand the barriers to earlier referral to palliative care for such patients. 18,19 The data also suggest that patients with low or no insurance had a higher number of palliative care visits, which is consistent with the findings of higher physical and psychosocial distress and higher risk of aberrant opioid use. At the same time, it is reassuring to find that insurance status was not a barrier to continued provision of palliative care services once access was established.…”
Section: Discussionsupporting
confidence: 82%
“…Lack of both standardised clinical pathways and systems for informationsharing have impeded the establishment of stable and integrated EOL care across relevant agencies [60]. Efforts to develop web-based system to monitor and refer patients have encountered multiple difficulties because of concerns about data security [61] and heterogeneity in illness trajectories [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…(119) In a systematic review of the literature to characterize referral criteria to outpatient palliative care for patients with cancer, 13 of 21 included studies specified symptom distress as a reason for referral. (120) Among these studies, ESAS was the most commonly used symptom assessment scale, with 7 of the 9 studies that reported the use of a validated scale employing ESAS. (121127) However, only one study stated a symptom intensity cutoff of ≥6/10 was needed to trigger a referral.…”
Section: Future Developmentsmentioning
confidence: 99%